2021
DOI: 10.3390/app11156976
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Absence of Lung Sliding in Lung Ultrasounds Using Deep Learning

Abstract: Certain post-thoracic surgery complications are monitored in a standard manner using methods that employ ionising radiation. A need to automatise the diagnostic procedure has now arisen following the clinical trial of a novel lung ultrasound examination procedure that can replace X-rays. Deep learning was used as a powerful tool for lung ultrasound analysis. We present a novel deep-learning method, automated M-mode classification, to detect the absence of lung sliding motion in lung ultrasound. Automated M-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There are already practical deployments of AI, e.g. , to help doctors to identify the heart failure problems ( Choi et al, 2016 ), lung problems after thoracic surgery ( Jaščur et al, 2021 ) or automatic detection of COVID-19 from lung ultrasound ( Born et al, 2020 ). However, the full potential of AI systems is limited by the inability of the majority of algorithms to explain their results and decisions to human experts.…”
Section: Explainability and Interpretabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are already practical deployments of AI, e.g. , to help doctors to identify the heart failure problems ( Choi et al, 2016 ), lung problems after thoracic surgery ( Jaščur et al, 2021 ) or automatic detection of COVID-19 from lung ultrasound ( Born et al, 2020 ). However, the full potential of AI systems is limited by the inability of the majority of algorithms to explain their results and decisions to human experts.…”
Section: Explainability and Interpretabilitymentioning
confidence: 99%
“…After clinical testing of a new procedure using lung ultrasound, the need arose to automate the diagnostic procedure. A study by Jaščur et al (2021) used DL in their work and created a new method that works with videos of lung ultrasound. The method consists of semantic segmentation of ultrasound images from the first images of the video.…”
Section: Xai In Video Processing Applicationsmentioning
confidence: 99%
“…Recently, to overcome the variability of POC ultrasound, machine learning (ML) and deep learning (DL) have been intensively investigated, which involves various tasks including classification, segmentation, detection, registration, regression, and quality assessment for lung (Correa et al 2018, Short et al 2019, Sonko et al 2019, Baloescu et al 2020, Born et al 2020, Jascur et al 2021. In the domain of POC lung ultrasound, several DL methods have been developed to quantitatively assess pulmonary congestion by measuring the total B-line score (BLS).…”
Section: Introductionmentioning
confidence: 99%
“…Javsvcur et al developed CNN models trained on a relatively small dataset of 28 positive clips and 20 negative clips to classify the presence of lung sliding and perform pleura segmentation. They achieved an accuracy of 89% (Jascur et al 2021). Recent studies and developments have demonstrated the clinical feasibility of DL models in lung sliding classification, achieving AUCs over 90%, even with well-curated M-mode data (VanBerlo et al 2022, Zhang et al 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation